In Vitro Screening of Fungicides and Plant Extracts Against Colletotrichum Gloeosporioides (Penz.) Sacc. the Causal Agent of Anthracnose Disease of Rauwolfia Serpentina (L.) Benth Ex Kurz (Journal of the Asiatic Society of Bangladesh, Science, 2019)
Ten fungicides viz., Amcogin 50 WP, Autostin 50 WDG, Capvit 77 WP, Dithane M 45, Greengel 72 WP, Haybit 80 WG, Oxivit 40 SC, Ridomil Gold MZ, Sulcox 50 WP and Tilt 250 EC at 100, 200, 300, 400 and 500 ppm concentrations were tested against, Colletotrichum gloeosporioides (Penz.) Sacc., the causal agent of anthracnose disease of Rauwolfia serpentina (L.) Benth ex Kurz following poisoned food technique. Amcogin, Autostin and Tilt showed complete growth inhibition of C. gloeosporioides at 100 ppm concentration. Ethanol extracts of ten plants viz., Adhatoda vesica, Azadirachta indica, Citrus limon, Curcuma longa, Lantana camara, Moringa oleifera, Ocimum sanctum, Psidium guajava, Thuja orientalis and Vitex negundo were selected to evaluate their efficacy at 5, 10, 15 and 20% concentrations against the same pathogenic fungus. Out of the ten plant extracts, Azadirachta indica, Citrus limon, Moringa oleifera and Psidium guajava showed complete radial growth inhibition of C. gloeosporioides at 20% concentration. Amcogin, Autostin, and Tilt are suggested as best inhibiting chemical fungicides for C. gloeosporioides. Extracts of A. indica, C. limon, M. oleifera and Psidium guajava were also found to be superior to other plant extracts tested in controlling the test pathogen.Asiat. Soc. Bangladesh, Sci. 45(1): 35-43, June 2019